Depoimento de defesa de Xanana Gusmão: a construção de um herói timorense - Miranda, Roberta Gonçalves de Sousa (2011)
Kay Rala Xanana Gusmão is one of the most important political figures of East Timor. His speeches have become known not only for its power of persuasion, but also the rich history and identity within it. Arrested in 1992, Xanana was put on trial farce-February-March 1993, at which he was denied the right to a lawyer. He defended his life and his destiny by using the best weapon available to him: the word. His "Testimony of Defense" is the object of this study noted that the construction of the subject of East Timor Xanana Gusmão, based on the procedures of discourse analysis (DA). Considering that the subject is constructed within the expository instance, at the time that the enunciator speaks and shows itself in his speech, the present study aimed to: a) identify and analyze linguistics choices made for the construction of the discourse, as that reveal clues about the Xanana s image; b) determine discursive and ideological formations, and c) identify elements that can help raise a characterization Timorese identity. To achieve the objectives, this research brief theoretical review presented on topics of discourse analysis (of particular interest with regard to the concepts of language, ideology and discourse), based in Fiorin (2003, 2008), Maingueneau (1997, 2008 ), Orlandi (2007, 2008, 2009) and Pêcheux (2009) and on Identity and National Identity, based on Hall (2006), Mattoso (1998) and Ortiz (2006); brief historical background of East Timor and Xanana Gusmão , which is crucial, since the stories of the author of the text studied and their country are intertwined. As a result of the research, the text-testimony proved to be valuable due to a number of features that allow the reader to identify Xanana as a hero. In many moments of discourse, he admits to be the leader and use his trial to fight in defense of their country. The East Timorese identity is revealed in several passages, through descriptions of national culture and social reality.